1997
DOI: 10.1002/(sici)1099-1646(199711/12)13:6<489::aid-rrr471>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of channel bed morphology in gravel-bed rivers using airborne multispectral imagery and aerial photography

Abstract: The potential for mapping in‐channel morphology within shallow gravel‐bed rivers using airborne multispectral imagery and aerial photography is illustrated using a case study from the River Tummel, Scotland. The technique described relies on a good correlation between observed light reflectance levels from a water body and water depth. Measured water depths are regressed against reflectance levels derived from airborne multispectral imagery and black‐and‐white aerial photographs, to obtain equations that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
173
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 7 publications
0
173
0
Order By: Relevance
“…Water depths were measured every 2 hours using a new noninvasive image-based dye density technique. The principle behind the technique is similar to one developed by Winterbottom and Gilvear [1997] using airborne multispectral imagery in natural rivers. We ran a 2 ppm (parts per million) solution of rhodamine dye through the flume and obtained vertical images with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…Water depths were measured every 2 hours using a new noninvasive image-based dye density technique. The principle behind the technique is similar to one developed by Winterbottom and Gilvear [1997] using airborne multispectral imagery in natural rivers. We ran a 2 ppm (parts per million) solution of rhodamine dye through the flume and obtained vertical images with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…That means that variations in valley width have not been driven 229 by modern bank and valley-wall erosion processes, but are from ancient processes of valley 230 aerial photographs Gurnell, 1997;Winterbottom and Gilvear;254 Winterbottom, 2000). Winterbottom and Gilvear (1997) showed that aerial photos can be used 255 to accurately quantify channel bed elevation, and Winterbottom (2000) found GIS an effective 256 and accurate tool in quantifying medium-and short-term channel changes on a wandering 257 gravel-bed river from survey maps and aerial photos. 258 259…”
Section: Persistence Of Riffle-pool Sequences 161mentioning
confidence: 99%
“…[5] Airborne multispectral remote sensing techniques have already been successfully applied to large-scale geomorphological work in fluvial environments [Winterbottom and Gilvear, 1997;Wright et al, 2000;Zhang, 2000;Legleiter et al, 2002]. These authors demonstrated that it is possible to classify morphological units in fluvial environments such as pools, riffles, and rapids from multispectral imagery with resolutions ranging from 0.25 to 3 m. Furthermore, an empirical method of automated grain size measurement using a combination of centimeter-resolution airborne digital color imagery and close range millimeter resolution imagery has been proposed by Verdú et al [2003].…”
Section: Introductionmentioning
confidence: 99%